Tennyson’s Selected Poems on Politics – An Overview - Karthikh, R.; Aungston, J. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Alfred Lord Tennyson is recognized as the most distinguished British poet of Victorian Age. His poems mostly explore the vital issues confronting Victorian England. He reveals his sense of political responsibility in his patriotic verses. His poems also reflect the descriptions of nature, his interest in science, religious and philosophical views, treatment of love and passion, etc. His poems Locksley Hall, The Charge of the Light Brigade, Sir Galahad, The Defense of Lucknow and The Revenge dominate the theme of political conditions of England in Tennyson’s Age. Hence this paper overviews the themes and arguments of Tennyson on politics and other social scenario of his age.
Keywords: Patriotism; Knighthood and Honour